Origins of the Iroquois League : Narratives, Symbols, and Archaeology - Wonderley, Anthony, 1949-; Sempowski, Martha L., 1942- (Book collections on Project MUSE., 2019)
"This is a scholarly work of anthropological archaeology in which Wonderley and Sempowski use their combined scholarship to shine a spotlight on what are perhaps the most significant yet neglected issues in the Iroquois past: When and how did historically known tribes begin to coalesce, what factors allowed the success of those population amalgamations, and when did the League of the Iroquois achieve its final form?"--